Etyczne wyzwania współpracy pomiędzy lekarzami a przemysłem farmaceutycznym - Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2011)
Over the recent years more and more often we can hear in public debate that pharmaceutical industry is using aggressive marketing to increase the market growth. Their marketing actions are addressed mainly to physicians, because doctors are those who raise gains of pharmaceutical companies in the most considerable extent. The main aim of this paper is to answer the question what kinds of methods pharmaceutical companies are using to influence physicians’ prescribing practice. On examples will be shown how pharmaceutical sales representatives are using reciprocity rule, liking, contrast, authority, scarcity, social proof and consistence to manipulate on doctors. The paper will try to answer the questions: Are physicians aware of influence of pharmaceutical companies? What should be done to increase their awareness? The article is based on the CAWI research. It is analysis of 372 questionnaires filled by physicians. Research was conducted with the support of Medycyna Praktyczna site – one of the most famous websites among the doctors in Poland.